Evaluation of antimicrobial activity of methanolic extract of flowering plants against pathogenic bacteria / Siti Khadijah Abdul Karim and Yasmin Said - Abdul Karim, Siti Khadijah; Said, Yasmin (Universiti Teknologi MARA, Negeri Sembilan, 2021)
Antimicrobials are a common term that refers to a group of drugs that can kill microorganism which antibiotic, antifungal and antivirus. Antimicrobial acts to inhibit the growth of microorganisms. Nowadays, there are minority of people that use traditional materials to treat a certain disease in this world. It can develop to be used as medicine and give benefits to other people. Since there is lacking information regarding to the flowering plants towards the antimicrobial activity, the study will elucidate the effect of antimicrobial activity that have in the extraction of flowering plants. The aim of study is to evaluate the potential of the antimicrobial activity in flowering plant extracts using disk diffusion method. The flowers used in this study are bougainvillea, frangipani and hibiscus flowers. Extracts from petals of flowers were obtained by using methanol extraction. The antimicrobial activity was carried out for antibacterial screening using E. coli and P. aeruginosa. All the flowers show large significantly different of inhibition zone for 24 hours of incubation in room temperature compared to negative control for E.coli. However, only bougainvillea flowers showed the higher inhibition zone which was 5.67 mm compared to positive control. The largest inhibition zone was showed in bougainvillea flower extracts for P. aeruginosa which was 4.67 mm. The smallest inhibition zone was showed in frangipani flower extracts compared to the negative controls. The result show different significant between the methanolic extract and controls. All the flowering plants extracts showed antibacterial test towards E. coli and P. aeruginosa. Bougainvillea flower extract shows largest inhibition zone compared to the other flowers' extracts. Hence, the methanol extract of Bougainvillea flower has a potential to be used as a good antibacterial agent.